DAMPAK INTERVENSI AKTOR-AKTOR EKSTERNAL DALAM MEMPENGARUHI DURASI PERANG SIPIL DI SURIAH - Muhammad Rizky Nur Kamrullah; Aspin Nur Arifin Rivai (UIN ALAUDDIN MAKASSAR, 2020)
This research aims to further explore the civil war that is taking place in Syria. This paper questions fundamentally, why did the civil war in Syria become a prolonged armed conflict? Or are there other factors that strengthen the strength of their resistance? This research offers a novelty of research on the situation of this conflict, is that the prolonged civil war in Syria is not only caused by internal conditions, but also the involvement of external actors. As with the approach of David E. Cunningham (2010) that the involvement of external actors in civil war produces two possibilities, namely; become a negotiating facilitator and help one party win. This research reveals that the involvement of external actors interventions - regional, international and transnational – actually prolongs the conflict. This is because the involvement of external actors causes the addition of combatants in the conflict, so the preference in the conflict increases. Keywords: Civil War, Assad Regime, Regional Actor, International Actor, and Transnational Actor.